Two way push videoenteroscopy in investigation of small bowel disease. Issue 2 (1st August 1998) - Bouhnik, Y; Bitoun, A; Coffin, B; Moussaoui, R; Oudghiri, A; Rambaud, J C
Abstract : Aims —To evaluate the diagnostic yield and safety of a new push type videoenteroscope (PVE) for diagnosis of small bowel disease. Methods —Three hundred and thirteen patients were referred for one or two way PVE from December 1993 to June 1996. Indications for PVE were: an unexplained iron deficiency anaemia with or without clinically evident gastrointestinal bleeding; or a complementary investigation for suspected small bowel disease, after a small bowel barium follow through (SBBFT) considered as normal or abnormal, but without a definite diagnosis. Results —A jejunoscopy and a retrograde ileoscopy were carried out in 306 and 234 patients, respectively. In patients with isolated anaemia (n=131) and those with clinically evident gastrointestinal bleeding associated anaemia (n=72), PVE provided a diagnosis in 26 (19.8%) and 22 (30.5%) cases, respectively. Lesions found were located in the jejunoileum in 30 (14.7%) patients and in the gastroduodenum or the colon in 18 (8.8%) patients—that is, within the reach of the conventional gastroscope/colonoscope. In patients with normal (n=54) or abnormal (n=56) SBBFT, PVE provided a diagnosis in 17 (31%) and 27 (48%) cases, respectively. In 25% of cases, the abnormal appearance of SBBFT was not confirmed. The site of the radiological abnormality was not reached in 27% of cases. Lesions were located at the jejunum and the ileum in 59 (64%) and 33 (36%) cases, respectively. Conclusions —PVE is useful in around 30% of cases of unexplained anaemia or after an SBBFT which failed to provide an accurate aetiological diagnosis. Use of retrograde videoenteroscopy increases diagnostic yield by one third.